Parental Involvement Among Junior High School Students in the New Normal Education (Ascendens Asia Singapore – Union Christian College Philippines Journal of Multidisciplinary Research Abstracts, 2026)
The COVID-19 pandemic has adversely impacted the conduct of education worldwide particularly in the Philippines, triggering an abrupt shift from face-to-face classes to online and home learning. The sudden change in the mode of delivery of instruction posed challenges not only among the affected students but also to their parents. The present study sought to determine the perceived parental involvement among the respondents in the new normal education context. The descriptive-correlational research design was utilized to analyze the parental involvement and academic success of 138 Junior High School students using a survey questionnaire. Weighted mean, frequency, percentage, and Pearson r correlation were employed for data analysis. Results showed that parents reported low involvement in the home education of their children in general. As to their participation to decision-making activities as members of the Parent Teacher Association, their involvement was perceived as moderate. Meanwhile, majority of the respondents have an academic performance above satisfactory. Parental involvement was not significantly correlated with the academic performance of students. In conclusion, parents were minimally involved in their children's home learning, and parental involvement is weakly correlated with academic performance. While the findings indicate strong self- regulation among students, parents are still encouraged to provide educational guidance and academic support to their child, being the first mentors in their educational journey.
Keywords: parental involvement; academic performance; new normal education